2015
DOI: 10.3390/f6082571
|View full text |Cite
|
Sign up to set email alerts
|

Wood Decay Fungi Restore Essential Calcium to Acidic Soils in Northern New England

Abstract: Abstract:The depletion of root-available calcium in northern forests soils exposed to decades of increased acid deposition adversely affects forest health and productivity. Laboratory studies indicated the potential of wood-decay fungi to restore lost calcium to the rooting zone of trees. This study reports changes in concentrations of Ca, Mg, and K during decay of sapwood of spruce, maple, hemlock, and birch at two locations in northern New England, USA. Concentrations of exchangeable Ca, Mg, and Al in decaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…For example, stems with higher Ca concentrations had slower decay rates, accounting for more than 20% of variation in the response. This finding does not fit the paradigm that calcium is a limiting nutrient in wood for fungal decomposers as others have found (Boddy, 1999; Shortle & Smith, 2015). Perhaps calcium has undiscovered direct negative effects on decomposer communities and/or activities, for example, by increasing the pH as has been studied using calcium hydroxide nanoparticles (Gioria & Osborne, 2014).…”
Section: Discussioncontrasting
confidence: 76%
“…For example, stems with higher Ca concentrations had slower decay rates, accounting for more than 20% of variation in the response. This finding does not fit the paradigm that calcium is a limiting nutrient in wood for fungal decomposers as others have found (Boddy, 1999; Shortle & Smith, 2015). Perhaps calcium has undiscovered direct negative effects on decomposer communities and/or activities, for example, by increasing the pH as has been studied using calcium hydroxide nanoparticles (Gioria & Osborne, 2014).…”
Section: Discussioncontrasting
confidence: 76%
“…Differential translocation of the ions prevalent in the fungal hyphae was observed indicating that fungi solubilize and transport ions from the soil to wood, and both into and out of the wood cell walls. The reasons for translocation and solubilization of some ions is not known, but for the oxidized forms of Fe and Mn it is well known that oxalate sequesters and solubilizes these ions, permitting mobilization and functional access to the organism 2 . Because of the increase in Fe during decay and the spatial control at both the bulk ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the role of ions in fungal degradation of woody biomass is salient to a wide range of research disciplines including carbon sequestration 1 2 , forest ecology 3 4 , plant pathology 5 , biorefinery 6 7 , basic fungal physiology 8 , and the durability and utility of wood in structural applications 9 10 11 12 13 . It is estimated that 10% of the lumber harvested each year is used to replace in-service wood that has been attacked by decay fungi 14 .…”
mentioning
confidence: 99%
“…Early studies recognized the importance of basic amino acids on the ligand that seemed critical for LRP1 receptor binding (Arandjelovic et al, 2005; Mahley et al, 1977; M. M. Migliorini et al, 2003; Prasad et al, 2016; Weisgraber et al, 1978). When the structure of two complement-like repeats (CR) from the LDL receptor in complex with the third domain of RAP (Fisher et al, 2006) was solved, a canonical model for ligand binding to LRP1 was revealed in which acidic residues from each CR formed an acidic pocket for in which two lysine side chains (K256 and K270) from RAP are docked.…”
Section: Discussionmentioning
confidence: 99%